2019
DOI: 10.5539/ibr.v12n9p62
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Mobile Banking Services Applications on Electronic Word of Mouth: The Mediating Role of Perceived Trust

Abstract: The objective of this study is to examine selected dimensions of mobile banking, (such as Ease of Navigation, Personalization Level, Information Quality, Rewards) on e-wom through the mediating role of perceived trust. Self-structured questionnaire is used to collect data which is then shared via Google forms online and targeted only to the users of mobile banking services application in Jordan. Quantitative and analytical methods were used to analyze the data. 499 questioners were returned, 30 of which were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…This result is supported by previous research(Giantari et al 2021;Mahadin and Akroush 2019).H6: Perceived Trust effect on Word of Mouth Perceived Trust has positive effect on Word of mouth with estimate LISREL value 0.24 and t-value > t-table (2.78 > 1.96) meaning that the cruise passengers who has trust the cruise operators will create word of mouth. This result is supported by previous research(Radiah et al 2021;Zalloum et al 2019). H7: Perceived Service Quality effect on Word of Mouth Perceived Service Quality has positive effect on Word of mouth with estimate LISREL value 0.35 and t-value > ttable (3.94 > 1.96) meaning that the cruise passengers who experienced good service quality then will create word of mouth.…”
supporting
confidence: 84%
“…This result is supported by previous research(Giantari et al 2021;Mahadin and Akroush 2019).H6: Perceived Trust effect on Word of Mouth Perceived Trust has positive effect on Word of mouth with estimate LISREL value 0.24 and t-value > t-table (2.78 > 1.96) meaning that the cruise passengers who has trust the cruise operators will create word of mouth. This result is supported by previous research(Radiah et al 2021;Zalloum et al 2019). H7: Perceived Service Quality effect on Word of Mouth Perceived Service Quality has positive effect on Word of mouth with estimate LISREL value 0.35 and t-value > ttable (3.94 > 1.96) meaning that the cruise passengers who experienced good service quality then will create word of mouth.…”
supporting
confidence: 84%
“…E-banking was one of the first applications of mobile commerce in the business world. Banks have developed their mobile applications to satisfy their picky clientele and provide effective, dependable, and prompt services (Zalloum et al, 2019). But banks have found that they must update it often and stay abreast of any new e-services (Abu Shanab & Abu Shanab, 2022;Hammouri et al, 2021).…”
Section: Respondentmentioning
confidence: 99%
“…This pervasiveness of mobile services prompted studies to explore mobility's impact on mobile service adoption as one of the main determinants (Zarmpou et al, 2012;Zalloum et al, 2019). Mobile services are independent of the user's physical location, the type of transaction, and the availability of ATMs.…”
Section: Mobilitymentioning
confidence: 99%